Unilateral Agenesis of the Upper Permanent Lateral Incisors in Growing Patients: Gap Closure or Gap Opening? A Systematic Review - Gianna Dipalma; Angelo Michele Inchingolo; Pietro Lauria; Pierluigi Marotti; Silvia Chieppa; Daniela Di Venere; Andrea Palermo; Massimo Corsalini; Francesco Inchingolo; Alessio Danilo Inchingolo (International Dental Journal, 2025)
Introduction: The optimal treatment for agenesis of maxillary lateral incisors is difficult to determine. The objective of this study was to determine, based on the evidence in the literature, the best treatment option for unilateral agenesis of upper lateral incisors, comparing the aesthetic and periodontal results of orthodontic closure of the space associated with canine camouflage versus the opening of the space and the subsequent placement of an implant, in the permanent dentition of growing patients. Materials and methods: Electronic databases (Scopus, PubMed, and Medline) were examined with the subsequent filters: English language; year of publication since 2012; humans. A manual screening of the reference lists of the potential studies was done. Risk of bias was measured by the Newcastle–Ottawa Scale. Results: The search found 379 publications, but 167 of them were duplicates, therefore, they were excluded. Titles and abstracts of 170 articles were accessed, and 128 were excluded. After applying the inclusion and exclusion criteria, 42 articles were fully reviewed, and 7 studies were included. Data were collected from the chosen articles and organized into a table for comparison and study of the results. In contrast to patients treated with implant, whose major disadvantage is infraocclusion, patients who received space closure and canine camouflage had better aesthetic and periodontal outcomes. Conclusion: Even if the best treatment option depends on the type of malocclusion of the patient, if both treatment alternatives are available, space closure is the better solution. However, because research samples are small and post-treatment evaluations are short, more prospective cohort studies are needed in the future to give better scientific evidence.